Consistent condom use and its predictors among female sexual partners of people who inject drugs in Klang Valley, Malaysia - Abdul Manaf, Rosliza; Dickson, Nigel; Lovell, Sarah; Ibrahim, Faisal (BioMed Central, 2019)
Background: Men who inject drugs (MWIDs) comprise the highest percentage of diagnosed HIV cases in Malaysia. Their female partners risk being infected through unprotected sexual contact. This paper reports the prevalence of consistent condom use and its predictors among the wives and regular sexual partners of MWIDs in Klang Valley, Malaysia. Methods: A cross-sectional study using a self-administered questionnaire was conducted among the wives and regular sexual partners of MWIDs in the study location; 221 women were recruited through respondentdriven sampling. Data were analysed descriptively for the prevalence of consistent condom use, HIV status and HIV risk-related behaviour. Subsequently, simple and multiple logistic regressions were undertaken to identify the predictors of consistent condom use. Results: The prevalence of consistent condom use among respondents was 19.5%. Slightly more than half (52.5%) of respondents had never used condoms with their partner. Fourteen women (6.3%) reported being HIV positive. While 7.7% had HIV-positive partners, 45.7% were unaware of their partner’s HIV status. Consistent condom use was significantly higher among single women (AOR = 4.95; 95% CI: 2.45, 9.99), women who lived in urban areas (AOR = 2.97; 95% CI: 1.30, 6.78), HIV-positive women (AOR = 3.45; 95% CI: 1.13, 10.5) and women involved in sex work (AOR = 3.55, 95% CI: 1.45, 8.67). Conclusions: Inconsistent condom use among the majority of female sexual partners of MWIDs underscores the heightened risk faced by these women and calls for alternative prevention methods that women are able to control.